The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4025/actascihealthsci.v42i1.52739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of horse riding equipment in activity of trunk and lower limb muscles in equine-assisted therapy

Abstract: Equine-assisted therapy uses the horse in rehabilitation and/or education of people, such as Down syndrome (SD), cerebral palsy (PC) and intellectual disability (DI). In context, the rehabilitation program and horse riding equipment should be used according to the specific characteristics of each individual, becoming an ally in the quest for excellence in equine-assisted therapy programs. The aim was to evaluate the effect of riding equipment used in equine-assisted therapy on the muscular activity of trunk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Studies with healthy individuals concluded that placing the feet in stirrups promoted greater muscle activation (Bravo Gonçalves Junior et al, 2020; Ribeiro et al, 2018). In another study, Down syndrome and intellectual disability groups presented greater neuromuscular activity of the trunk and lower limbs without the feet supported in the stirrups, whereas a cerebral palsy group presented greater neuromuscular activity with the feet supported in the stirrups (Lage et al, 2020). In our study, there was no significant difference in the body trunk musculature when the feet were inside or outside the stirrups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies with healthy individuals concluded that placing the feet in stirrups promoted greater muscle activation (Bravo Gonçalves Junior et al, 2020; Ribeiro et al, 2018). In another study, Down syndrome and intellectual disability groups presented greater neuromuscular activity of the trunk and lower limbs without the feet supported in the stirrups, whereas a cerebral palsy group presented greater neuromuscular activity with the feet supported in the stirrups (Lage et al, 2020). In our study, there was no significant difference in the body trunk musculature when the feet were inside or outside the stirrups.…”
Section: Discussionmentioning
confidence: 95%
“…We did not include any exercises during the sessions to evaluate only the effect of the horse's three-dimensional movement on the rider. A previous study with a cerebral palsy group showed greater neuromuscular activity of the trunk with the feet supported on the stirrups, while participants with Down syndrome and intellectual disability showed greater neuromuscular activity without the stirrups (Lage et al, 2020). However, as we did not find studies with older adults, we used a saddle with feet in the stirrups for the first 15 minutes and out of the stirrups for the remaining 15 minutes of a 30-minute session.…”
Section: Introductionmentioning
confidence: 98%
“…Inferindo a necessidade de ajustes tônicos e aumento da força muscular para se manter sentado sobre o cavalo. A escolha do material de montaria de acordo com o comprometimento físico e Research, Society and Development, v. 10, n. 7, e10410716198, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i7.16198 ou intelectual do sujeito e com o objetivo terapêutico proposto, é de fundamental importância para alcançar resultados positivos, enfatizados em estudos descritos na literatura que avaliaram o aumento da atividade elétrica muscular, por meio do eletromiográfo de superficie, a utilização de alguns materiais de montaria e a colocação ou não dos pés nos estribos para diversos processos patológicos gerais (Laje et al, 2020;Fernandes et al, 2018;Espindula et al, 2014). A força é sustentada por uma combinação de fatores morfológicos e neurais, incluindo a área e arquitetura da seção transversal muscular, rigidez musculotendinosa, recrutamento da unidade motora, codificação da taxa, sincronização da unidade motora e inibição neuromuscular.…”
Section: Discussionunclassified
“…It is worth mentioning that, during the entire data collection period, the two horses were kept according to the fi rst care of each child, respecting the moments of rest and rest as a guarantee of the animal's health conditions. The horse riding equipment used was the blanket (made of foam and covered with synthetic leather) with front range for upper limb support and without foot support in the stirrups 22 .…”
Section: Methodsmentioning
confidence: 99%